Changes of the Lithuanian Periodical Structure (1988-1995) - Genovaitė Burneikienė (Knygotyra)
The article gives survey of the genesis of the Lithuanian periodicals and analyses the process of press development (in 1988 through 1995). The article deals with the conditions that determined emergence of the uncensored press of Sąjūdis movement during the Resurgence period (in 1988). The article reveals impact of publications of Sąjūdis movement on the Lithuanian society and the official press (in 1988 appeared about 70 publications of Sąjūdis movement) and the ways used by local individual editorial offices to disengage from "care" of the periodical press of the Communist Party.